2009 Ninth IEEE International Conference on Bioinformatics and BioEngineering 2009
DOI: 10.1109/bibe.2009.34
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Endodontic Treatment for Periapical Lesions in Intraoral Radiographs

Abstract: Intraoral radiographs have been taken to diagnose periapical lesions. Subsequent endodontic treatment needs to be evaluated quantitatively, that is often difficult due to various imaging factors as well as subjective visual interpretation. Therefore, we sought to establish an image analysis based quantitative model to evaluate endodontic treatments (40 effective and 43 noneffective cases). To normalize an image, the dentin area and the background were used as references. In each pair of images representing bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
4
2
Order By: Relevance
“…Using Equation (4), as derived from the results, the accuracy of detection of apical lesions based on the technique presented on this paper has been success-fully increased to 92.75%. This is in contrast to the study in [23] which reported an accuracy of 80.7%. In [23], TOPHAT technology was used to crop the periapical, and the model was determined by logistic regression analysis.…”
Section: Resultscontrasting
confidence: 94%
See 3 more Smart Citations
“…Using Equation (4), as derived from the results, the accuracy of detection of apical lesions based on the technique presented on this paper has been success-fully increased to 92.75%. This is in contrast to the study in [23] which reported an accuracy of 80.7%. In [23], TOPHAT technology was used to crop the periapical, and the model was determined by logistic regression analysis.…”
Section: Resultscontrasting
confidence: 94%
“…This is in contrast to the study in [23] which reported an accuracy of 80.7%. In [23], TOPHAT technology was used to crop the periapical, and the model was determined by logistic regression analysis. Although this study showed a significant improvement.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…34,35 On periapical lesions, Mol and van der Stelt reported one of the early studies on periapical bone defects, detecting the lesions semiautomatically and characterizing their size via texture analysis. [36][37][38] More recently, Li et al 39 and Lee et al 40 introduced semiautomatic CAD methods for segmentation of periapical/bifurcation lesions by level-set method and for detection of bone remodeling at treated sites by logistic regression, respectively. However, these studies neither address the differential diagnosis between granulomas and cysts nor deal with 3D CT data.…”
Section: C Related Workmentioning
confidence: 99%